2021
DOI: 10.3389/fvets.2021.650546
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Dermanyssus gallinae? Genetic Structure of Populations and Critical Synthesis of the Current Knowledge

Abstract: Despite the economic and animal welfare importance of the Poultry Red Mite Dermanyssus gallinae, its genetic structure has been studied in a scattered way so far. The prophylaxis and control of such a globally distributed ectoparasite can be significantly improved by understanding its genetic population structure (composition in species and intraspecific variants). The present study aims to establish a rigorous framework for characterizing the neutral genetic structure of D. gallinae based on a literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…In addition, some differences among the four populations under test may be explained by the strong genetic differentiation among D. gallinae populations that develop on poultry farms in France and United Kingdom (Roy et al, 2021): the attractive response occurred at higher concentration in English populations than in French populations (5% vs. 0.25%-1%) and we recorded significant differences in locomotor activity between English and French populations.…”
Section: Validation Of the Mitemap Systemmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, some differences among the four populations under test may be explained by the strong genetic differentiation among D. gallinae populations that develop on poultry farms in France and United Kingdom (Roy et al, 2021): the attractive response occurred at higher concentration in English populations than in French populations (5% vs. 0.25%-1%) and we recorded significant differences in locomotor activity between English and French populations.…”
Section: Validation Of the Mitemap Systemmentioning
confidence: 79%
“…Tested individuals of D. gallinae (adult females; length: 0.75–1.5 mm) were collected from several laying hen farms: two French farms (DIN, Pierrelatte; DG‐FR10) and two British farms (DG‐UK04; DG‐UK05) to compare populations assumed to be reproductively isolated for a long time (UK vs. France) or not (within each country) (Roy et al, 2021 ). In this context, we consider as a population a set of individuals that live in a given farm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous genotyping of several successive batches of dozens of mites randomly sampled at different locations and times in farm DIN showed that the poultry red mites that develop in this farm only belong to D. gallinae s.s. (more precisely, 100% of the genotyped individuals carried haplotypes of the haplogroup C, very common in French layer farms). 27 Selection of mites to be inoculated into the mesocosms was performed under a stereomicroscope, retaining the largest mites to form a 100% female inoculum as in Bartley et al 28 Only live and active mites were collected, using a P1000 filter pipette tip connected to a vacuum pump. The tips were then sealed with parafilm.…”
Section: Biological Materialsmentioning
confidence: 99%
“…The poultry red mite (PRM), Dermanyssus gallinae (De Geer, 1778) (Acari, Dermanyssidae), is a common ectoparasitoid that feeds on poultry and human blood, and is highly prevalent in poultry farms worldwide, causing annual losses of millions of Euros ( 1 ). PRM are tiny, hiding in cracks in the walls of poultry houses and chicken coops during the day, and sucking blood from the host at night.…”
Section: Introductionmentioning
confidence: 99%